2009
DOI: 10.1128/jb.01527-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Hemolysin-Like Proteins Similar to RTX Toxin in Pasteurella pneumotropica

Abstract: Pasteurella pneumotropica is an opportunistic pathogen that causes lethal pneumonia in immunodeficient rodents. The virulence factors of this bacterium remain unknown. In this study, we identified the genes encoding two RTX toxins, designated as pnxI and pnxII, from the genomic DNA of P. pneumotropica ATCC 35149 and characterized with respect to hemolysis. The pnxI operon was organized according to the manner in which the genes encoded the structural RTX toxin (pnxIA), the type I secretion systems (pnxIB and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…However, the virulence factors of bacterial infection in laboratory animals have not been thoroughly studied. Recently, we described the identification and characterization of the RTX toxins [19,21]. The P. pneumotropica animal model developed in this study will be useful for investigating virulence factors such as RTX toxin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the virulence factors of bacterial infection in laboratory animals have not been thoroughly studied. Recently, we described the identification and characterization of the RTX toxins [19,21]. The P. pneumotropica animal model developed in this study will be useful for investigating virulence factors such as RTX toxin.…”
Section: Discussionmentioning
confidence: 99%
“…We are currently investigating the virulence factors of P. pneumotropica. In our previous studies, several RTX toxins have been identified in these bacteria [19,20]. Furthermore, several candidate virulence-associated genes such as RTX toxins were identified from a draft genome sequence of P. pneumotropica [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The strain possessed outermost surface materials, which may be pili, on the bacterial cells and belonged to group two based on biochemical and genetic characteristics [17,18]. This strain produces RTX toxins PnxIA, IIA, and IIIA, and its draft genome sequence has been revealed [19,20]. The strain was thawed from frozen stocks (-80°C) and grown overnight on 5% horse blood agar plates (Sanko Junyaku Co. Ltd, Tokyo, Japan) and checked for purity.…”
Section: Preparation Of P Pneumotropica Inoculummentioning
confidence: 99%
“…In current studies, several RTX (repeats in toxin) toxins were identified in this species, and of these, 250-kDa PnxI-IIA contains bacterial Ig-like domains and hemagglutinin repeats that are thought to be indispensable for the protein's attachment and invasion of bacterial cells into host organs [15,16]. In fact, the recombinant PnxIIIA that lacks these domains failed to bind to the extracellular matrix (ECM) [16].…”
Section: Introductionmentioning
confidence: 97%
“…In fact, the recombinant PnxIIIA that lacks these domains failed to bind to the extracellular matrix (ECM) [16]. PnxIIIA is reportedly less cytotoxic toward leukocytes as compared to other RTX family proteins, and therefore, PnxIIIA is one of the candidate antigens for immunization against P. pneumotropica infection in rodents [15,16]. In this regard, ECM adhesive proteins help long-term retention in the nasal cavity, which results in enhanced opportunities for NALT cell recognition when PnxIIIA is used in a vaccine for intranasal immunization.…”
Section: Introductionmentioning
confidence: 99%